PENGARUH MODEL PROBLEM SOLVING BERBASIS KONTEKSTUAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN HASIL BELAJAR KOGNITIF SISWA - Siti Mariana; Siti Nurhidayati; Septiana Dwi Utami (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: The purpose of this research are: 1) To know the influence of problem solving model based on contextual problem solving ability class VII SMPN 04 Kopang, 2) To know the influence of contextual model based on contextual learning of cognitive learning grade VII SMPN 04 Kopang. Research this study is Quasi experimental, with the design used is pre-test posttest nonequivalent control group design. Sampling technique used saturated sampling, so the class VIIA with the number of students 27 people as experimental class and class VIIB with the number of students 27 people as a control class. The research instrument consisted of data of problem solving test result in the form of test essay and cognitive learning result of the student in the form of multiple choice test. The data analysis technique of this research use the teded-t polledvarian for student problem solving and t separatedvarian-t test for students' cognitive learning outcomes. The result of research are: 1) Obtained average score of problem solving ability of experiment class problem is 49 is in good category and control class is 34 is in less good category while result of t test is t-count> t-table (24,28> 2,000), then Ha accepted Ho is rejected, (2) Data cognitive learning results obtained t-count> t-table (3.248> 2.056), then Ha received Ho is rejected, thus can be concluded that: 1) There is influence using problem solving model based on the contextual ability of problem solving students, 2) There is influence of using problem-solving model based on contextual to student cognitive learning outcomes.